2022
DOI: 10.1037/men0000379
|View full text |Cite
|
Sign up to set email alerts
|

The Conformity to Masculine Norms Inventory-30: Validity and measurement invariance of a Russian-language version.

Abstract: The research presented here reports the process of adapting the Conformity to Masculine Norms Inventory (CMNI) for use in Russian. The full-and short-form (CMNI-30) versions of the Inventory were tested in two studies. In total, 681 Russian residents participated in Study 1 and 716 in Study 2, which investigated the unidimensional, 10-factor, second-order, and orthogonal bifactor models. The analysis of construct validity indicated that the full version of CMNI did not fit the data. Therefore, we developed a R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
0
9
2
Order By: Relevance
“…We preferred this approach over using latent scores to reflect the CMNI's use in practice. Although subscale scores were originally calculated by summing up each subscale's item scores, different researchers and practitioners also use the items' means (e.g., Krivoshchekov et al, 2022), and no consistent guidelines or norms for the CMNI exist. Following Levant et al (2020), we chose to report the sums of the items instead of the means.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We preferred this approach over using latent scores to reflect the CMNI's use in practice. Although subscale scores were originally calculated by summing up each subscale's item scores, different researchers and practitioners also use the items' means (e.g., Krivoshchekov et al, 2022), and no consistent guidelines or norms for the CMNI exist. Following Levant et al (2020), we chose to report the sums of the items instead of the means.…”
Section: Methodsmentioning
confidence: 99%
“…We are aware of only one study exploring measurement invariance of the CMNI across different sexual orientation groups (Krivoshchekov et al, 2022), though notably, that study used a somewhat different version of the CMNI-30 and with a Russian sample. In their study, Krivoshchekov et al (2022) tested several potential models with the items that survived Levant et al's (2020) 2022) established partial scalar invariance across heterosexual and sexual minority men, after allowing the intercepts to vary in one item ("I bring up my feelings when talking to others"). The authors concluded that overall, the two groups have similar understandings of the items in their version.…”
Section: Measures Of Masculinity Norms and The Cmnimentioning
confidence: 99%
“…Most studies on TM have been based on research involving men living in English-speaking countries. Nevertheless, research within and outside English-speaking countries demonstrated gender, sexuality, age, ethnic, and national differences (e.g., Komlenac & Hochleitner, 2022;Komlenac et al, 2023;Krivoshchekov et al, 2021Krivoshchekov et al, , 2022; R. F. Levant, 2011; R. Levant & Richmond, 2007).…”
Section: Traditional Masculinitiesmentioning
confidence: 99%
“…Higher scores indicated greater disgust towards meat (current study α = .88). Traditional masculinity was measured with the 30-item Conformity to Masculine Norms Inventory Short Form(Levant et al, 2020), which has been validated cross-culturally in US(Levant et al, 2020) and Russian samples(Krivoshchekov et al, 2022) of straight and sexual minority men. Although the CMNI-30 is best used as a multidimensional rather than unidimensional scale, there is too little evidence in the literature to indicate which specific masculine norms should correlate with meat consumption, therefore the total scale was used.…”
mentioning
confidence: 99%